2016
DOI: 10.12738/estp.2016.1.0281
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Self-Regulated Learning Strategies of Students from the Faculty of Education Using Ordinal Logistic Regression Analysis

Abstract: Citation: Bozpolat, E. (2016). Investigation of the self-regulated learning strategies of students from the faculty of education using ordinal logistic regression analysis. AbstractThe purpose of this study was to reveal whether the low, medium, and high level self-regulated learning strategies of third year students at the Education Faculty of Cumhuriyet University can be predicted by the variables of gender, academic self-efficacy, and general academic average. The study uses the Relational Screening Model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
(20 reference statements)
1
11
1
8
Order By: Relevance
“…These concepts are inter-related. Previous studies have shown that general academic averages can predict levels of self-regulated learning (Bozpolat, 2016) and that the use of metacognitive skills are positively correlated to academic achievement in various disciplines (Hakan, 2016). While some evidence exists to support the hypothesis that SRL and metacognitive abilities relate to ultimate academic achievement, the interdependency of both and any possible impact on the grade point average (GPA)s of final year pre-service elementary teaching candidates in Turkey has yet to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…These concepts are inter-related. Previous studies have shown that general academic averages can predict levels of self-regulated learning (Bozpolat, 2016) and that the use of metacognitive skills are positively correlated to academic achievement in various disciplines (Hakan, 2016). While some evidence exists to support the hypothesis that SRL and metacognitive abilities relate to ultimate academic achievement, the interdependency of both and any possible impact on the grade point average (GPA)s of final year pre-service elementary teaching candidates in Turkey has yet to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it has been found that there is a significant and a negative-sided relationship between teacher candidates' problem solving appraisal and the utilization of motivated strategies for learning for the departments Social Studies Education, Primary Education, Turkish Language Education and Elementary Math Education. Considering the self-regulating individuals use more strategies (Zimmerman, 1990; as cited in Bozpolat, 2016) and primary self-regulative processes are related to effective problem solving process (Çelik-Ercoşkun & Köse, 2014) and also self-confidence about own skills is related to more effective problem solving (Bloom & Broder, 1950;as cited in Heppner, 1978), the finding that there is a negative-sided and a significant relationship between teacher candidates' problem solving appraisal and the utilization of motivated strategies for learning for the departments except Elementary Science Education and Early Childhood Education can be interpreted as following. As teacher candidates' appraisal of their problem solving increase, their tendency to utilize motivated strategies for learning might have been decreased for the departments except Elementary Science Education and Early Childhood Education because of their probably unrealist appraisal of their own problem solving skills.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, as learners get used to discover different meanings of words or structural forms in an inductive way from authentic data (i.e., corpus), they start to gain more autonomy, thus enabling them to use self-regulating strategies or gradually to control their own learning process. According to a recent study, Bozpolat (2016) found a positive relationship between self-regulated learning strategies and having high self-efficacy and high academic performance. In the interviews conducted in the present study, learners in the DDL group made similar arguments, lending greater support to DDL, such as "I felt responsible myself" and "DDL left me to work and to learn on my own."…”
Section: Discussionmentioning
confidence: 99%